PENGARUH KONSUMSI JUS TOMAT JERUK NIPIS TERHADAP KADAR KOLESTEROL TOTAL PADA WANITA DEWASA USIA 40-60 TAHUN - Ika Fitria Ningtyas; Kun Aristiati Susiloretni; J Supadi (Poltekkes Kemenkes Semarang, 2017)
Background : Dyslipidemia is a lipid metabolism disorder, which is characterized by increased or decreased lipid fraction in the blood of increased total cholesterol levels, LDL cholesterol, triglycerides, and decreased HDL cholesterol. Patients with dyslipidemia tend to have a higher risk of atherosclerosis. Objective : This study aimed to determine the effect of tomato lime juice on total blood cholesterol levels 0-60 years old women. Methods : This was true experiment study designed with randomized pre and post test control group design. The samples of this study were women aged 40-60 years were not diagnosed dyslipidemia with cholesterol total ≥150 mg / dl. The treatment group received tomato lime juice, for the control group did not get special treatment. The treatment study conducted for 21 days. Measurement of cholesterol levels before and after treatment using cholesterol test, blood sample retrieved after subject of the study had fasting for 10 hours long. Statistical analysis difference of post cholesterol content between treatment and control group analyzed by independent t-test. Multiple linear regression test ware used for predict the effect of nutrition intake toward cholesterol total level. Result : In the study of nutritional status of the sample included in the category of obesity (60.5%). The nutrient intake included in the deficit category. Total cholesterol levels in both groups before intervention did not differ (p = 0.937). Bivariate analysis, The treatment and control group of the study have difference in total cholesterol decreasing (p = 0.024). The mean decrease of cholesterol level in treatment and control group which are 18.35 mg / dl and 12.06 mg / dl. Multivariate analysis, cholesterol levels controlled with intake did not differ (p0.05) Conclusion : The tomato lime juice treatment affects the total cholesterol levels in the 40-60 years old women.